DNA, brain, mind, and soul according to Christian Teaching - Lee, Paul (Studia Bioethica, 2017)
It is a very interesting and familiar concept of soul and familism in Confucianism. Concept of qi, hun and po sounds somewhat similar but different from Christian concept, and the Confucian concept of family after death is different from Christian’s. Let me briefly describe some differences in Christian teachings from Confucianism in reference to a human nature and after death.